PMFEB-KIPKU: Pelatihan Pembukuan Sederhana bagi UMKM Majelis Taklim Mesjid Al-Muhajirat Kelurahan Biring Romang Kecamatan Manggala Kotamadya Makassar - Asri Usman; Baso Siswadarma; Nariswhari Arisani Asri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Low levels of financial literacy and poor financial management practices are still the main problems faced by micro, small and medium enterprises that are based on community and religious organizations. Problems with unorganized financial recording systems, in addition to the inability to separate business from personal finances, are obstacles to obtaining financing as well as making appropriate business decisions. The community service program is intended to improve the financial management capacity of micro, small and medium enterprises based at the Al-Muhajirat Mosque Taklim Assembly in Biring Romang Village, Makassar City through practical training on basic accounting. The method used is lectures, tutorials, and discussions tailored to the needs of partners with a participatory approach. The evaluation was carried out using participatory observation, case studies as well as post-training assessments to measure the effectiveness of the program. The results showed a significant increase in participants' ability to record transactions, implement a simple accounting cycle, and separate business from personal finances. Participants can also prepare basic financial reports for decision-making purposes. This program strengthens MSMEs' readiness for more accountable, transparent, and sustainable financial management.